The Aesthetics of African Sculpture and Ceramics: The Aesthetics of African Sculpture and Ceramics (Journal of Humanitarian and Applied Sciences, 2025)
African sculpture and ceramics possess a unique visual and aesthetic identity that represents the collective spirit and spiritual beliefs of African people. it is not merely decorative but integral part of daily life, religious, and social rituals. African sculpture is unique by combing simple forms and complex symbols simultaneously. Ceramics, on the other hand, represent the functional and aesthetic aspect of daily life in Africa and is an art often practiced by women. It is distinguished by its unique designs and shapes that express the values, beliefs, and environment of African societies.The research concludes that African sculpture is linked to spiritual rituals that is used as symbols to document historical events and honor certain figures. The sculptural works are characterized by simplicity and harmony, relying on materials available in their environments. African vessels are used for storing food and water, as well as in religious, funerary and celebratory rituals.
Keywords: African sculpture; spiritual rituals